The Degree of Application of eadership Talent Management Strategies in the Jordanian Ministry of Education from the Point of View of the Principals of Public Schools in the University District - Aeda Tubaileh (Deanship of Scientific Research (DSR), the University of Jordan, 2020)
This study aims to find out the degree of application of leadership talent management strategies in the Jordanian Ministry of Education from the point of view of the principals of public schools in the university District. The study followed the descriptive survey method, and the sample of the study consisted of (99) directors in the university District in Amman. To achieve the objectives of the study, the researcher built a questionnaire consisting of (43) paragraphs distributed over four areas. The study showed the following results: The estimations of the principals of the public schools for the degree of applying the leadership talent management strategies in the Jordanian Ministry of Education from the point of view of the principals of the public schools in the university District are high in all fields (leadership talent development, retaining leadership talent, succession leadership, motivating leadership talent). The results also showed that there were no statistically significant differences in the estimates of public school principals to the extent of applying the leadership talent management strategies in the Jordanian Ministry of Education attributed to the effect of both educational level and educational qualification variables. In the light of the results of the study, the researcher recommended the following: The necessity of the Ministry of Education to pay attention to placing leadership talents in important leadership positions appropriate to their capabilities.